The girl from the other side : Siuil, a Run. 1 - Nagabe; Beck, Adrienne; MacFarlane, Ysabet Reinhardt ([Los Angeles] : Seven Seas Entertainment, 2016)
"In a world split between the Inside and the Outside, those living in both realms are told never to cross over to the other side, lest they be cursed. A young girl named Shiva lives on the other side, in a vacant village with a demonic guardian known only as 'Teacher.' Although the two are forbidden to touch, they seem to share a bond that transcends their disparate appearances. But when Shiva leaves Teacher's care to seek out her grandmother, the secret behind her mysterious living arrangement comes to light."--Provided by publisher.
Translation of: Totsukuni no shojo.
Reads from right to left in the traditional Japanese format.
"All Ages"--Back cover.
Young Adult
Keywords: Imaginary places -- Comic books, strips, etc. -- Juvenile fiction; Human-animal relationships -- Comic books, strips, etc. -- Juvenile fiction; Imaginary places -- Fiction; Human-animal relationships -- Fiction; Fantasy comics; Graphic novels